PENGEMBANGAN E-MODUL BERBASIS WEB DAN KAHOOT PADA MATA PELAJARAN BAHASA INDONESIA SISWA KELAS V SD - Alimashur, Akhmad; Denna Delawanti Chrisyarani; Dwi Agus Setiawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
With the advancement of technology in education, teachers and students can now quickly search for and access various scientific information through the internet. Technology-based media in the learning process offer numerous benefits for both educators and learners. This study aims to develop a web-based E-Module integrated with the Kahoot application as an interactive learning medium for fifth-grade elementary students in Indonesian language subjects. The background of this research is based on the learning conditions at SDN Trawas 2, where instruction is still dominated by lecture methods and the use of student worksheets (LKS), with limited utilization of digital technology, resulting in relatively low student motivation, participation, and comprehension. This research employed the R&D method using the ADDIE model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. The resulting product is an interactive E-Module containing learning materials, summaries, practice questions, and Kahoot-based learning games. Validation results from media, content, and language experts indicated that the product was highly feasible, with percentages of 96.4%, 98%, and 100%, respectively. The practicality test showed highly practical results, with scores of 97.2% from teachers, 95.5% from the small group, and 94.6% from the large group. The effectiveness test conducted through pretest and posttest yielded an N-Gain score of 80.9%, categorized as effective. Therefore, the web-based E-Module integrated with Kahoot is considered valid, practical, and effective in improving student learning outcomes, as well as in supporting active, enjoyable learning aligned with the Merdeka Curriculum and the demands of 21st-century education.